Ocena alfabetyzmu zdrowotnego studentów na podstawie kwestionariusza Health Literacy Questionnaire (HLQ) – badania wstępne - Leksy, Karina; NawóJ-Połoczańska, Joanna; Skowrońska-Pućka, Agnieszka (Studia Edukacyjne, 2023)
The World Health Organization defines health literacy as the cognitive and social skills that determine people’s motivation and ability to gain access to, understand, and use information in ways that promote and maintain good health. Health literacy is closely linked to health behavior, health inequalities, and overall quality of life. It is also highly connected with health socialization and education in the home and school environment. Considering the importance of this concept, this study aims to preliminary examine the university students’ health literacy based on the Health Literacy Questionnaire (HLQ). The research was conducted from March to May 2023 among students of the Faculty of Social Sciences of the University of Silesia in Katowice and the Faculty of Educational Studies of Adam Mickiewicz University, Poznań. Research results have shown that, in general, the health literacy of surveyed students was high. The respondents found actively taking care of their health the hardest task. Simultaneously, most of them declared receiving social support in health. Monitoring the level of health literacy is crucial for providing important information about the needs of various groups in health awareness and contributes to undertaking educational activities in this area.